2018
DOI: 10.3389/fmicb.2018.00904
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Rumen Bacteria and Protozoa Through Grazing Regime as a Tool to Enhance the Bioactive Fatty Acid Content of Bovine Milk

Abstract: Rumen microorganisms are the origin of many bioactive fatty acids (FA) found in ruminant-derived food products. Differences in plant leaf anatomy and chemical composition between cool- and warm-season pastures may alter rumen microorganisms, potentially enhancing the quantity/profile of bioactive FA available for incorporation into milk. The objective of this study was to identify rumen bacteria and protozoa and their cellular FA when cows grazed a warm-season annual, pearl millet (PM), in comparison to a dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…The proportions of anteiso-C15:0 and C15:0 observed in the current study are largely consistent with those in the fermented mixtures (aneiso-C15:0, 24.7-29.6%; C15:0, 24.9-27.9%) after 21 h of incubation in vitro with four types of dairy diet as substrates [1] as well as in the rumen bacteria (aneiso-C15:0, 23.76%; C15:0, 25.7%) collected from Holstein cows under different feeding regimes [23,24]. Vlaeminck et al [25] reported a close relationship (r = -0.77) between anteiso-C15:0 concentration and dietary forage inclusion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The proportions of anteiso-C15:0 and C15:0 observed in the current study are largely consistent with those in the fermented mixtures (aneiso-C15:0, 24.7-29.6%; C15:0, 24.9-27.9%) after 21 h of incubation in vitro with four types of dairy diet as substrates [1] as well as in the rumen bacteria (aneiso-C15:0, 23.76%; C15:0, 25.7%) collected from Holstein cows under different feeding regimes [23,24]. Vlaeminck et al [25] reported a close relationship (r = -0.77) between anteiso-C15:0 concentration and dietary forage inclusion.…”
Section: Discussionsupporting
confidence: 87%
“…With increasing supplementary levels of forage in the diets, total OBCFA production has been reported to be linearly increased in the study of Vlaeminck et al [25], whereas quadratically changed in rumen contents at 6 h after the morning feeding as observed by Zhang et al [3] which is partially in line with our data. As known, the OBCFA, especially BCFA, mainly derive from bacteria and meanwhile are the unique components of cell membrane lipids in kinds of bacteria [4] ; and exist in rumen protozoa as well [23,24]. Therefore, the increasing OBCFA production obtained in the present study might indicate the microorganisms were keeping a strong reproducibility and proliferation during the whole in vitro incubation, which would be bene cial for microbial metabolic process and fermentation activities.…”
Section: Discussionmentioning
confidence: 49%
“…This family is composed of both fibrolytic organisms and members involved in starch hydrolysis, which could produce acetate, formate, succinate, and so on (36). In this study, compared with Prevotella is a known starch and protein utilization bacteria (39) and has the highest abundance in the rumen of lactating dairy cows and may be altered in responding to different diets and feeding patterns (40,41). Prevotella has enzymes that degrade xylan and other hemicelluloses into SCFA, such as acetate, propionate or propionate-precursor succinate (35).…”
Section: Prevotella Ruminococcus Eubacterium and Other Members Of mentioning
confidence: 93%
“…Valerate is one of the products resulting from the degradation of branched amino acids and itself serves as an important precursor for synthesizing odd branched-chain fatty acids [6]. It has also been suggested that odd branched-chain fatty acids could be synthesized by elongating propionate [41]. Hence, it is reasonable to observe positive correlation between Succiniclasticum abundance and concentrations of propionate, isovalerate, valerate, and total BCVFA due to vital roles of this genus in fermenting succinate to propionate and degradation of protein [12,40].…”
Section: Correlations Between Ambient Temperature Physiological and mentioning
confidence: 99%